Naturally Derived Malabaricone B as a Promising Bactericidal Candidate Targeting Multidrug-Resistant Staphylococcus aureus also Possess Synergistic Interactions with Clinical Antibiotics - Neethu Sivadas; Grace Kaul; Abdul Akhir; Manjulika Shukla; Murugan Govindakurup Govind; Mathew Dan; Kokkuvayil Vasu Radhakrishnan; Sidharth Chopra (MDPI AG, 2023)
The emergence of multidrug-resistant (MDR) superbugs underlines the urgent need for innovative treatment options to tackle resistant bacterial infections. The clinical efficacy of natural products directed our efforts towards developing new antibacterial leads from naturally abundant known chemical structures. The present study aimed to explore an unusual class of phenylacylphenols (malabaricones) from Myristicamalabarica as antibacterial agents. In vitro antibacterial activity was determined via broth microdilution, cell viability, time-kill kinetics, biofilm eradication, intracellular killing, and checkerboard assays. The efficacy was evaluated in vivo in murine neutropenic thigh and skin infection models. Confocal and SEM analyses were used for mechanistic studies. Among the tested isolates, malabaricone B (NS-7) demonstrated the best activity against S. aureus with a favorable selectivity index and concentration-dependent, rapid bactericidal killing kinetics. It displayed equal efficacy against MDR clinical isolates of S. aureus and Enterococci, efficiently clearing S. aureus in intracellular and biofilm tests, with no detectable resistance. In addition, NS-7 synergized with daptomycin and gentamicin. In vivo, NS-7 exhibited significant efficacy against S. aureus infection. Mechanistically, NS-7 damaged S. aureus membrane integrity, resulting in the release of extracellular ATP. The results indicated that NS-7 can act as a naturally derived bactericidal drug lead for anti-staphylococcal therapy.